Non- Bank Islamic Mortgage in Maqashid al-Sharia Perspective - Fahmi Syam; Afifuddin Kadir; Ayuesha Nur Salma (Universitas Islam Negeri Alauddin Makassar, 2020)
Home mortgage or KPR is regarded as an alternative answer for possessing a house recently, Home mortgage should be possible either through Conventional bank and sharia bank. However, recently there have been new alternatives of owning home by using non-bank Islamic mortgage. Where the mortgage can presently be directly handled by the developer without involving the bank. The issues of this Paper are describing the opinion that non-Bank Islamic Mortgage is more sharia than Islamic Banking in providing Islamic Housing, such as no BI Checking, no riba, no fines, no confiscation, and etc. The purpose of this research is to identify the scheme of non-bank Islamic Mortgage, and analyse the scheme in Maqasid Sharia perspective as Importance foundation in religion. The methods in this study are descriptive analysis research. The data used is secondary data and data collection techniques are literature studies. After discussing, the results showed that Non-Bank Islamic Mortgage cause a lot of harm in term of customer and sharia developer it self in Maqāsid Sharia perspective.